Pembuatan Database Murid TK Aisyiyah Busthanul Athfal 5 Mataram - erlina sasanti, elin; animah, animah; suhaedi, wirawan; Astuti , Widia; ridhawati, rini (Institut Agama Islam Hamzanwadi NW Pancor, 2024)
Abstract Administration is very important for the world of education with the aim that the management and regulation of school data can be structured systematically so that it is easily accessible to interested parties. Aisyiyah Busthanul Athfal 5, Mataram, has not yet implemented database management using computer. Based on these problems, Excel-based school management application training to help the school solve existing problems. Implementation of training creating a school database using Excel will be held in 2 sessions with a target number of participants of 15 people. Participants in this training consist of operators or school administration staff and school teachers. The results of this activity include several components, namely the participants' ability to master the material, the material targets that have been planned, success in the target number of training participants, and achievement of the training objectives. The achievement of the objectives of introducing Computer Based Reports is good